Innovation and Regulation: Legal Enablers and Challenges in Indonesia’s Digital Banking Lending Ecosystem - Anastasia Zefanya (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study aims to analyze the impact of the Financial Services Authority (OJK) Regulations No. 13/POJK.02/2018, No. 12/POJK.03/2021, and No. 10/POJK.05/2022 on banking participation in technology-enabled lending, in conjunction with the enactment of Law No. 27/2022 on Personal Data Protection and Law No. 4/2023 on the Development and Strengthening of the Financial Sector. The research employs a normative-juridical approach to examine the evolution and implementation of regulatory sandboxes, digital Know – Your – Customer (e-KYC) procedures, and AI-based credit scoring mechanisms. These elements are assessed in terms of their legal foundations and practical implications for credit accessibility, operational efficiency, and financial inclusion. The findings reveal that while these regulatory advancements have significantly improved access to credit and enhanced the efficiency of digital financial services, several challenges remain. These include a rise in non-performing loans, vulnerabilities in data privacy and cybersecurity, opaque interest rate structures, and compliance gaps in anti-money laundering and counter-terrorism financing (AML/CTF) frameworks. Addressing these issues requires the development of a risk-based, technology - neutral regulatory framework, increased transparency in algorithmic decision-making, and stronger cross-sector collaboration. Such measures are essential to fostering a robust, secure, and inclusive digital lending ecosystem in Indonesia that balances innovation with consumer protection and systemic stability.